Challenges of peace Education model for effective industrial relations and workplace harmony (2007)
Despite the statutory mechanisms set lip to settle industrial conflicts. the persistent reoccurrence calls for an alternative approach to solving them. It is against this background that this paper is proposing the use of Peace Education as an alternative approach to promoting industrial harmony at the workplace. The paper looked at the different notions of peace, causes of industrial conflict and the concept of peace education. 1t further posited that Peace Education consist of acquisition of certain knowledge, attitudes and skills to be used to scan the national and international environment in which the workplace is cited in order to prevent the internal and external sources of conflict. Two models on peace education were discussed. The system model so developed for the implementation of Peace Education at industrial level shows that work organizational environment and goals are no longer seen as a multitude of" separate objectives but as one indivisible, dynamic whole, whose parts are all inextricably interrelated. Furthermore, when the model is operationalized .both labour and management will no longer be at logger head but mutual partnersworking towards the survival of both parties.